Physico-chemical justification and experimental verification of a waste-free method of oxidative dephosphorization of a high-phosphorus manganese alloy - Kamkina , L.V.; Velychko , K.O.; Velychko , O.G.; Zhouhua, Jiang (Theory and Practice of Metallurgy, 2024)
The purpose of the study: physicochemical justification of the process conditions and development of a rational algorithm for a single-stage waste-free method of oxidative dephosphorization of a high-phosphorus manganese alloy. Methods: thermodynamic analysis of the main reactions during oxidative refining of manganese alloys with a high phosphorus content. Experimental verification of the main stages of refining. Results: The physicochemical essence of the refining process of a high-phosphorus manganese alloy, which consists in creating conditions for oxidation in the alloy of manganese, carbon and silicon, is considered. The thermodynamic forecast of the course of reactions under the given conditions of oxidative refining of the associated metal confirms the possibility of obtaining three products: low-phosphorus manganese slag, ferric melt and phosphorus-containing slag with a phosphorus oxide content of 18-20% (phosphorus fertilizer). Scientific novelty: Based on the results of high-temperature mathematical modeling, it was established that the most rational oxygen consumption, which ensures the achievement of the tasks, is ~ 13 m3. As an oxidant, it is advisable to use oxygen blown by air, which is introduced into the converter bath using an inflatable nozzle from above. In this case, the total air consumption per 100 kg of alloy should be about 50 m3. Practical value: In the work, based on the thermodynamic forecast of the behavior of the elements of the accompanying alloy in oxidizing conditions, assessment of the thermal side of the process and further experimental verification, results were obtained that confirm the possibility of creating a waste-free technological scheme for refining a high-phosphorus alloy. In this case, it is advisable to carry out the refining of the alloy in conditions close to the conditions of modern production of low-phosphorus manganese slag, in which the temperature of the accompanying alloy is 1320...1350°C.